2020
DOI: 10.1186/s13014-020-01671-8
|View full text |Cite
|
Sign up to set email alerts
|

Proton pencil beam scanning reduces secondary cancer risk in breast cancer patients with internal mammary chain involvement compared to photon radiotherapy

Abstract: Purpose Proton pencil beam scanning (PBS) represents an interesting option for the treatment of breast cancer (BC) patients with nodal involvement. Here we compare tangential 3D-CRT and VMAT to PBS proton therapy (PT) in terms of secondary cancer risk (SCR) for the lungs and for contralateral breast. Methods Five BC patients including supraclavicular (SVC) nodes in the target (Group 1) and five including SVC plus internal-mammary-nodes (IMNs, Group 2) were considered. The Group 1 patients were planned by PT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Furthermore, while our facility was mainly designed for heavy ions, the proton beam focus width for low energy is known to be larger than cyclotron-based centers. However, despite this fact, and most probably linked to the use of a smaller range shifter (only 2 cm) compared to other facilities for shallow target treatments (between 5 and 7 cm), no compromise in the quality of our plan between target coverage and sparing of OAR was needed, and our dosimetric and NTCP predictions were similar to other published work [44][45][46][47][48], as shown in Tables 6 and 7. 4.2 (1.9-5.9) 1.1 (0.3-1.3)…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, while our facility was mainly designed for heavy ions, the proton beam focus width for low energy is known to be larger than cyclotron-based centers. However, despite this fact, and most probably linked to the use of a smaller range shifter (only 2 cm) compared to other facilities for shallow target treatments (between 5 and 7 cm), no compromise in the quality of our plan between target coverage and sparing of OAR was needed, and our dosimetric and NTCP predictions were similar to other published work [44][45][46][47][48], as shown in Tables 6 and 7. 4.2 (1.9-5.9) 1.1 (0.3-1.3)…”
Section: Discussionsupporting
confidence: 79%
“… 104 Other studies have reported similar benefits when combining DIBH and IMPT in left-sided cancers requiring supraclavicular and IMC nodal irradiation. 107 , 108 Other factors should be taken into consideration when combining DIBH with protons. For example, a major advantage of combining DIBH with IMPT is that DIBH will minimize the dose variation from the interplay effect, which is defined as the difference between the absorbed dose volume during motion and when stationary.…”
Section: Additional Heart Sparing Techniquesmentioning
confidence: 99%
“…Growing interest has been registered in recent years toward radiotherapy-induced toxicity, including late effects such as secondary cancer induction. In this context, special attention is deserved for instance by paediatric, lymphoma and breast cancer patients treated with protons, according to the comparably good survival and long-life expectancy (Cella et al 2013, Abo-Madyan et al 2014, Cartechini et al 2020, Paganetti et al 2020. This is also relevant for particle beams heavier than protons, whose use is prospectively increasing.…”
Section: Survival Parameters Mutation Parametersmentioning
confidence: 99%
“…Further developments of the present work are on-going and include the application of the RBE M ˜to the estimation of SCR after proton therapy plans. Specifically, for this aim, SCR models proposed in the past and recently tested also by our group can be expanded (Schneider and Walsh 2008, Schneider 2009, Cartechini et al 2020, taking into account at the same time the impact of a variable RBE for both cell survival and mutation induction. In the context of the current discussion on the clinical use of a variable RBE in proton therapy, this may contribute to shed light on the risks of side effects related to this technique and thus also to improve the patient selection procedure.…”
Section: Survival Parameters Mutation Parametersmentioning
confidence: 99%
See 1 more Smart Citation